Analyzing the Influence of the Commuter Rail in Decongesting Roads in Nairobi: A Case Study of Syokimau Commuter Rail Service - AbdulHakim Mwalimu Makarani; Simpson N Osano; Francis J Gichaga (LPPM Universitas Andalas, 2024)
Nairobi, the capital city of Kenya is experiencing road traffic congestion which gets worse at peak times. Amongst, the interventions tried to help reduce the congestion is the introduction of commuter rail services. However, almost 11 years after commissioning the usage of the service is still very low and the roads are still experiencing congestion. The aim of this study is to determine the influence of the commuter rail service in decongesting the roads in Nairobi. The study made use of questionnaires to determine the stakeholders’ perception on the influence of travel cost, travel time, convenience and reliability in attracting them to the usage of the commuter rail. The results indicate a direct relationship on the influence of travel time, travel cost, convenience and reliability of the commuter rail to decongestion of roads. The improvement of the travel aspects of time, cost, convenience and reliability is expected to attract users to the commuter rail in effect reducing road transport users leading to less congestion on the roads